East facing temple complex entrance - Temples of India Project Team (Jio Institute, 2024)
View of the modern dharmashala (a charitable public rest house or shelter) rooms added surrounding the verandah (open-air hallway or porch) of the Suswani Mata temple complex. The shikhara (superstructure) of the main temple and the flagstaff of the centrally located old temple are visible from the open ground in front of the main gate.